PENERAPAN STRATEGI ACTIVE LEARNING TIPE THE FIRING LINE DALAM PEMBELAJARAN BIOLOGI KELAS VIII SMPN 1 RANAH BATAHAN KABUPATEN PASAMAN BARAT - Sartika, Lesi; Susanti, Diana; Megahati, RRP. (Pendidikan Biologi, 2014)
ABSTRACT The essential of learning is a process of communication between teacher-students and also students to students.  In  addition,  the  inappropriate  of  using  teaching  strategy  will  make  students  bored  in accepting the material so it will be difficult for students to understand and finally their mark is low. The low result of students can be influenced by two factors such as external and internal of students self. The dominant factor come from students interested in learning. One of the way to solve the problem is implementation active strategy type the firing line. The aim of this research is to know the effect of active learning strategy type the firing line in biology learning class VIII SMPN 1 Ranah Batahan Kabupaten West Pasaman. The type of this research is experimental research with randomized control group posttest only design. The population of this research is student class VIII the first semester  SMPN  1  Ranah  Batahan  academic  year  2013/2014  which  consist  of  three  class.  The technique of sampling is used purposive sampling, as VIII4  experimental class and VIII2 as control class. The instrument use objective test as 24 score. The analysis of data is done by t-test, with criterion tcalculate  > ttable. Based on the analysis, the range of experimental class is 74,1 with branching off standard 11,9, meanwhile the range of control class is 58,8 with branching off standard 9,4. In analysis of t-test, it can be gotten tcalculate (4,87) > ttable (2,08) so it can be concluded that, the learning process with active learning strategy type the firing line increase result of biology of student class VIII SMPN 1 Ranah Batahan.